Identifikasi Senyawa Metabolit Sekunder Ekstrak Etanol Kulit Buah Pisang Kepok (Musa paradisiaca L) dengan Metode KLT - Hasma Hasma; Winda Winda (Jurnal Kesehatan Manarang, 2019)
Indonesia is a country that is rich in abundant natural plants by having various types of plants which have medicinal properties and are used by some people as traditional medicines. One use of traditional medicine used by the community is the banana plant. So far the community only uses bananas, limited to the use of their fruit, then the banana peel after consumption is only disposed of as waste that is not used optimally by the community. This study aims to identify the chemical compounds found in the skin of Kepok Banana (Musa paradisiaca L) taken from the pioneer road in the city of Makassar. This identification is carried out using the Thin Layer Chromatography (TLC) method and chemical reagents. Kepok banana peel extract (Musa paradisiaca L.) is made using maceration method, because the method is not only simple, the equipment used is simple, easy to work on, can also avoid damage to compound components due to heat. The yield of Rendamen obtained was 12.06%. Identification was done using Silica Thin Layer Chromatography GF254 with N-hexane eluent: ethyl acetate (6: 4) eluents obtained 5 stains on 366 nm UV light, namely alkaloids with orange blotches with Rf value (0.13), saponins with blemishes. purple Rf value (0.92), flavonoids with yellow spots Rf values ​​(0.33) and tannins with blackish orange patches Rf values ​​(0.65). Based on testing using chemical reagents obtained positive results saponins, flavonoids, tannins and alkaloids. The conclusion of the study showed that the Kepok banana peel extract taken on the pioneering road of Makassar city contained alkaloids, saponins, flavonoids and tannins.